Engine Lubricant Impact in Light-Vehicle Fuel Economy: A Combined Numerical Simulation and Experimental Validation - Fernando Fusco Rovai; Eduardo Sartori; Jesuel Crepaldi; Scott Rajala (Lubricants)
The optimization of passenger car efficiency is an important contribution to GHG emissions mitigation. This global warming concern is pushing technological solutions to reduce vehicle fuel consumption and consequently CO2 emissions. In this work, the impacts of engine lubricants with lower viscosity and friction modifier additive in a light-vehicle with a spark ignition engine were numerically simulated and experimentally validated. The substitution of a baseline 5W40 lubricant by a lower viscosity 5W20 proposal resulted in 2.9% lower fuel consumption in a combined cycle. This fuel consumption improvement is enhanced to 6.1% with a 0W16 lubricant with friction modifier. A 1D simulation model based on lubricant temperature and viscosity impact on engine friction was developed and presented good experimental correlation in combined cycle for 5W20, showing a 7% lower fuel consumption advantage than the experimental results. The numerical simulation advantage was 38% lower than experimental results for 0W16 that contains friction modifier, as the additive impact was not considered in this mathematical model.